2017
DOI: 10.5863/1551-6776-22.6.412
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Barriers and Facilitators at Affect Community Pharmacists' Ability to Engage Children in Medication Counseling: A Pilot Study

Abstract: OBJECTIVESThis study aimed to describe the barriers and facilitators that influence community pharmacists' ability to provide medication counseling to pediatric patients.METHODS Semistructured interviews (n = 16) were conducted with pharmacy staff at 3 community pharmacies in 2 Eastern states. The interview guide elicited pharmacy staff experiences interacting with children and their perceived barriers and facilitators to providing medication counseling. Transcripts were reviewed for accuracy and a codebook wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…21 Pharmacists have reported that they communicate with children approximately 30% of the time and that often only parents are present when pediatric prescriptions are picked up. 33,[35][36][37] Consequently, mainly parents receive medication information regarding their child's prescription from pharmacists. 33,35 Children's absence during medication pick-up may reduce opportunities for direct pharmacist-child communication.…”
Section: Discussionmentioning
confidence: 99%
“…21 Pharmacists have reported that they communicate with children approximately 30% of the time and that often only parents are present when pediatric prescriptions are picked up. 33,[35][36][37] Consequently, mainly parents receive medication information regarding their child's prescription from pharmacists. 33,35 Children's absence during medication pick-up may reduce opportunities for direct pharmacist-child communication.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists recognized the importance of the FMSP as a communication tool to encourage patients to ask questions to make consultation more interactive and engaging. Prior research has indicated the lack of pharmacist-child consultation in community pharmacies, highlighting the importance of the FMSP in facilitating pharmacists in discussing important medication details with both parents and children [ 24 ]. However, pharmacists utilizing this tailored approach may face barriers, such as time constraints and the absence of children in community pharmacies [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists' interventions focused on children should be performed using different resources such as demonstrative and interactive games preferably mediated by electronic devices (cell phones, tablets, and so on) as well as child-friendly educational materials. 73,[92][93][94] The adaptation of the pharmacist's work process to reach the target audience (how the intervention is performed) is essential to ensure the effectiveness of the intervention. 73 Some of the key components of the interventions found in this review, such as health education (on the disease, pharmacotherapy "and" or "or drug administration), clinical monitoring, and asthma control are also performed by other health professionals such as community agents, nurses, and physicians.…”
Section: Discussionmentioning
confidence: 99%